2020
DOI: 10.1021/acsomega.0c03174
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printed Lightweight Composite Foams

Abstract: The goal of this paper is to enable three-dimensional (3D) printed lightweight composite foams by blending hollow glass microballoons (GMBs) with high density polyethylene (HDPE). To that end, lightweight feedstock for printing syntactic foam composites is developed. The blend for this is prepared by varying the GMB content (20, 40, and 60 volume %) in HDPE for filament extrusion, which is subsequently used for 3D printing. The rheological properties and the melt flow index (MFI) of blends are investigated for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…It is also seen that the tensile stiffness and strength of the 3D-printed PLA foams in this research have an increasing trend with increases in density. A similar stiffness–density variation trend was reported for tensile strength in References [ 13 , 14 ], while a decreasing trend was observed for stiffness in those references.…”
Section: Materials Testing and Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It is also seen that the tensile stiffness and strength of the 3D-printed PLA foams in this research have an increasing trend with increases in density. A similar stiffness–density variation trend was reported for tensile strength in References [ 13 , 14 ], while a decreasing trend was observed for stiffness in those references.…”
Section: Materials Testing and Resultssupporting
confidence: 86%
“…One category of porous polymeric structures is syntactic foams, which use hollow spheres in their matrix. Syntactic foams have been in use since the 1950s, and have thus been the focus of extensive research [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Customised characteristics can be achieved for many applications by varying the volume percentage of these hollow fillers in the matrix (Gupta and Ricci, 2006). H S et al (2020) produced lightweight syntactic foam composites by mixing various content of micro glass balloons (GMBs) with high-density polyethylene (HDPE) using the MEX process and studied their rheological and mechanical properties. The results showed that the foam specimens produced have higher specific tensile and flexure modulus in comparison to pure HDPE.…”
Section: Introductionmentioning
confidence: 99%
“…Spherical fillers and inorganic or organic fibers, as well as the addition of amorphous PP, have shown positive effects with respect to the warpage of PP and PP copolymers. In contrast to PP or random PP copolymers, much less is known regarding the extrusion-based additive manufacturing of PE. Chinga-Carrasco et al reported on the fabrication and 3D printing of HDPE biocomposites reinforced with compatibilized thermo-mechanical pulp (TMP) fibers. , Various studies have also shown the usability of recycled HDPE from postconsumer waste, which once again underlines the outstanding position of polyethylene in terms of sustainability. The authors often point out that the printing of pure HDPE is associated with poor adhesion and unacceptable warpage . In a recent advance, our group has shown that these problems associated with FFF of HDPE can be solved by selecting a suitable printing build plate and by optimizing the printing parameters to fabricate parts that exhibit mechanical properties similar to those obtained by conventional injection molding .…”
Section: Introductionmentioning
confidence: 99%
“…38−41 The authors often point out that the printing of pure HDPE is associated with poor adhesion and unacceptable warpage. 42 In a recent advance, our group has shown that these problems associated with FFF of HDPE can be solved by selecting a suitable printing build plate and by optimizing the printing parameters to fabricate parts that exhibit mechanical properties similar to those obtained by conventional injection molding. 43 Moreover, several groups have employed UHMWPE as an additive for the 3D printing of PP and ABS/poly(styrene-block-ethene-co-butene-block-styrene) (SEBS).…”
Section: Introductionmentioning
confidence: 99%